Relationship between self-disclosure to first acquaintances and subjective well-being in people with schizophrenia spectrum disorders living in the community - Yokoyama, Kazuki (PLoS One, 2019)
OBJECTIVE: Focusing on people with schizophrenia spectrum disorders living in the community, the present study aims to examine the characteristics of and gender differences in self-disclosure to first acquaintances, and to clarify the relationship between self-disclosure and subjective well-being. METHODS: Participants (32 men and 30 women with schizophrenia spectrum disorders) were examined using the subjective well-being inventory, an original self-disclosure scale for people with mental illness, as well as the Rosenberg self-esteem scale, the Link devaluation-discrimination scale, and the affiliation scale. RESULTS: The self-disclosure content domains in descending order were as follows: “living conditions,” “own strengths,” “experiences of distress,” and “mental illness and psychiatric disability.” There were no significant gender differences in self-disclosure in the total and domain scores. Multiple regression analyses by gender revealed that: (1) in men, decreasing feelings of ill-being were significantly predicted by self-disclosure about “living conditions,” self-esteem, and perceived stigma; (2) in women, increasing feelings of well-being were significantly predicted by self-disclosure about “own strengths,” self-esteem, and sensitivity to rejection. CONCLUSIONS: Self-disclosure to first acquaintances was related to subjective well-being in people with schizophrenia spectrum disorders living in the community. This result supports the recovery model and the strengths model. It suggests the importance of interventions targeting self-disclosure to first acquaintances about experiences as human beings, such as “living conditions” and “own strengths,” as it relates to subjective well-being in community-based mental health rehabilitation.